Progress of NiO‐Based Anodes for High‐Performance Li‐Ion Batteries. Issue 10 (24th June 2022) - Zhou, Guolang; Ding, Wenhao; Guan, Yu; Wang, Tianshi; Liu, Cheng; Zhang, Lili; Yin, Jingzhou; Fu, Yongsheng
Abstract: Rechargeable lithium‐ion batteries (LIBs) are of great significance to the development of renewable energy. The traditional graphite anode is gradually unable to meet increasing demands for high energy density and power density due to its low theoretical capacity. NiO has gained considerable attention because of its high theoretical capacity, low toxicity, and stable chemical properties. This review summarizes the research progress of NiO‐based nanomaterials in LIBs and centers on the electrochemical reaction mechanism, synthesis methods, and strategies for improving the electrochemical properties of NiO anodes. The results demonstrate that the electrochemical characteristics highly depend on the synthesis method, morphology, surface area, conductive substrate, etc. Compared with pure NiO, NiO‐based composites including NiO/carbon‐based materials and NiO/metal oxide often present higher capacity and cycle stability. Furthermore, challenges and future perspectives of NiO‐based anodes are also discussed. Abstract : This review summarizes the research progress of NiO‐based nanomaterials in LIBs and centers on the electrochemical reaction mechanism, synthesis methods, and strategies for improving the electrochemical properties of NiO anodes. Challenges and future perspectives of NiO‐based anodes are also discussed.